IMPORTANCE OF ISLAMIC FINANCIAL SERVICES ACT 2013 IN TAKAFUL INDUSTRY AFTER THE REPELLED TAKAFUL ACT 1984 - Siti Norshila Jamil; Jasri Jamal (Diponegoro Law Review, 2016)
The new Malaysian Islamic Financial Services Act 2013 (Act 759) (‘IFSA 2013’) came into force on the 30th June 2013. Its main objectives are to promote financial stability and compliance to Shariah and further strengthen the regulation of Islamic financial institutions. By this, the IFSA 2013 aims to strengthen consumer protection and further increase the confidence of the public in Takaful. At the same time, it remains to be seen if the IFSA 2013 will also encourage Takaful Operators to take their social and religious responsibility more into consideration, which is fundamental behind the concept of Takaful.  Keywords: Takaful, Islamic Financial Services Act 2013